Pengaruh Kejelasan Sasaran Anggaran, Sistem Pelaporan, Audit KInerja dan Pengendalian Akuntansi terhadap Akuntabilitas Pengelolaan Dana Desa - Elisabet Rina Anggraini; Jaka Darmawan (Jurnal Ekonomi Pembangunan, 2020)
TThis study aims to determine the effect of Clarity of Budget Objectives, Reporting Systems, Performance Audit, and Accounting Control on the Accountability of Village Fund Management in tiyuh located in Tulang Bawang Tengah, Tumijajar, Tulang Bawang Udik district. The population in this study was a village officials involved in the management of village funds located in tiyuh-tiyuh, Tulang Bawang Tengah District, Tumijajar, Tulang Bawang Udik. The number of village officials in the village is 105 people. And the number of samples that can represent the population to be studied is as many as 74 sample respondents who will be studied. The method of determining the sample is using a simple random sampling method. The data collection method used was a questionnaire. And the data analysis technique used is Multiple Linear Regression Analysis. Based on the results of this study, it shows that the clarity of budget targets, the reporting system affects the accountability of village fund management in the Kecamatan Tulang Bawang Tengah, Tumijajar, Tulang Bawang Udik. Meanwhile, performance audits and accounting controls do not affect the accountability of village fund management in Tulang Bawang Tengah, Tumijajar, Tulang Bawang Udik sub-districts. This shows that the better the clarity of budget targets and the reporting system, the better the accountability of village fund management in Tulang Bawang Barat Regency.